Determinan Minat Beli Konsumen Produk Usaha Mikro Kecil dan Menengah (UMKM) di JakPreneur - Mahmud Mahmud; Sarpan Sarpan; Endri Sentosa; Ilham Kudratul Alam (Oikonomia: Jurnal Manajemen, 2022)
Purpose The purpose of this study is to determine the factors that influence consumer buying interest in MSME products at Jakpreneur, which is devoted to three variables, namely brand image, product quality, and packaging design. Methodology This study is an associative quantitative study and was tested with multiple regression. Data were collected by distributing questionnaires to respondents who were the research sample, namely UMKM consumers in Jakpreneur, East Jakarta. The sampling technique was accidental sampling and sample measurement techniques were based on the provisions of the experts set by the researchers for 100 respondents. Findings The results showed that there was a positive and significant influence of brand image, product quality and packaging design on consumer buying interest in MSME products at Jakpreneur. Of the three research variables, the most influential variable on consumer buying interest in MSME products at Jakpreneur is the packaging design variable. Suggestions for SMEs in Jakpreneur, especially East Jakarta, should pay attention to and improve their packaging design, both in terms of color, model or shape.